EPIDEMIOLOGY FORECASTING ANALYSIS OF DENGUE HAEMORRAGHIC FEVER WITH SEASONAL AUTOREGRESSIVE INTEGRATED MOVING AVERAGE IN TROPICAL AREA - Siswanto, Siswanto; Risva, Risva; Marliana, Nana (YCAB Publisher & IAKMI SULTRA, 2019)
Background: Health problems that often occur in tropical countries are infectious diseases, one of which often causes outbreaks was Dengue Hemorrhagic Fever (DHF). This disease often causes problems especially in endemic areas and even outbreaks that occur with death from sufferers.Objectives: To forecasting of the Dengue Hemorrhagic Fever in the working area of the Puskesmas Temindung. Methods: This was analytical descriptive research with forecasting design using secondary data and primary from informant who understand the problem. Forecasting using SARIMA method (Seasonal Autoregressive Integrated Moving Average).Results: The results showed that the total of DHF cases in Temindung Health Center could be predicted by the SARIMA (1,1,1) (1,0,0) model with means square error (MSE) of 0.001394688 forecasting results obtained from October 2018 to September 2019 cases, which tend to fluctuate but illustrates an increase in cases of DHF compared to the previous year's data. Conclusion: Forecast of the DHF is for the next 12 months starting from October 2018 as many as 7 cases, in November 4 cases, in December 4 cases; then starting in January 2019 as many as 3 cases, February 2 cases, March 3 cases, April 3 cases, May 3 cases, June 4 cases, July 3 cases, August 3 cases and September 3 cases with a total number of 42. Forecasting results show dengue cases tend to fluctuate every month but have increased cases from the previous year.